2021
DOI: 10.4081/ejtm.2020.9302
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus syndrome: COVID-19 psychotrauma

Abstract: The authors propose term “coronavirus syndrome” for the mental disorder that is a psychical response to the global problem of COVID-19 pandemic. This syndrome will affect up to 10% of the population and we could already observe acute stress reactions to the spread of the infection and changes in people’s ordinary lifestyle. However, the most severe response will be seen later, in this case the catastrophe is similar to the clinical picture of post-traumatic stress disorder. The problem is that coronavirus synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Manifestations may include obsession and compulsion, reduced social activity, poor concentration, aggression, irritability, substance use, and cognitive deficit [ 37 ]. Post-traumatic stress disorder; a psychiatric condition induced by life-stressing factors, could occur after recovery from a life-threatening illness, including COVID-19; as shown by recent studies, the prevalence rate may range from 5.8% to 43% [ 25 , 41 , 42 , 43 ]. Neurological post-COVID complications have also been reported, including late-onset Guillain-Barré syndrome, opsoclonus-myoclonus syndrome, acute transverse myelitis.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Manifestations may include obsession and compulsion, reduced social activity, poor concentration, aggression, irritability, substance use, and cognitive deficit [ 37 ]. Post-traumatic stress disorder; a psychiatric condition induced by life-stressing factors, could occur after recovery from a life-threatening illness, including COVID-19; as shown by recent studies, the prevalence rate may range from 5.8% to 43% [ 25 , 41 , 42 , 43 ]. Neurological post-COVID complications have also been reported, including late-onset Guillain-Barré syndrome, opsoclonus-myoclonus syndrome, acute transverse myelitis.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…This has increased the risk of mental health problems such as anxiety, depression, and stress [ 6 , 7 , 8 , 9 ]. Several longitudinal studies have already shown that national “lockdowns” during the early phases of the pandemic had a negative impact on people’s mental health and subjective well-being [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This case-fatality rate explains PTSD symptoms in COVID-19 survivors due to fear or imminence of death. Similarly, confinement can be configured as a stressor and not necessarily a formal traumatic event (Soloveva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%